ANALISIS FINANSIAL INDUSTRI KOPI TERIPANG JAHE (KOTEJA) DI PROVINSI BENGKULU - Dinanty, Diah; Dewi, Kurnia Herlina; Mujiharjo, Sigit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
Sea cucumber ginger coffee are coffee herbs made of sea cucumber as well as material additional ginger. Hence required planning coffee industry sea cucumber ginger on a commercial scale in the province of bengkulu and necessary a way to determine the feasibility (NPV, IRR, Net B/C Ratio, PBP, BEP and analysis sensitivity) coffee industry sea cucumber ginger .The result of this research is coffee industry sea cucumber ginger located in kabupaten rejang lebong Bengkulu, with capacity production 9.100 kg per month or 395.642 sachets per month selling price 1900 persachet and with of these capacity so obtained financial aspects coffee sea cucumber ginger namely NPV Rp 1.439.792.088 , IRR 37,888 %, Net B/C Ratio Rp 2,124, BEP 3.536.156 sachets , PBP 2 years eight months, it was stated that the coffee industry sea cucumber ginger worthy of to be developed toward an industry that commercial.